2015
DOI: 10.5617/jmi.v2i1.882
|View full text |Cite
|
Sign up to set email alerts
|

Models and Streams of Data Journalism

Abstract: This paper presents the initial results of a two-year research project, Data Journalism Work Practices, which focuses on newsrooms in Finland, the UK and the US. Data journalism or data-driven journalism has been defined simply as journalism based on large data sets (Rogers 2011;Bounegru et al. 2012.) According to our ongoing research on data journalism work methods, we can claim this has been an oversimplification. Based on six interviews of leading Finnish, American and British data journalists we can claim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 8 publications
0
39
0
6
Order By: Relevance
“…In many cases, journalists with advanced knowledge and skills in working with data science are the exception rather than the norm [Bra11]. To make data science more easily accessible for journalists in a more general sense, such tools need to utilize simple and easy‐to‐understand visual interfaces that cater to the exploratory nature of the journalists' activities, for example to allow the incorporation of unconfirmed data that can be used for further investigation [KCCW09, UK15]. A prominent example of such a tool is Overview which allows journalists to analyze large bodies of documents [BISM14].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In many cases, journalists with advanced knowledge and skills in working with data science are the exception rather than the norm [Bra11]. To make data science more easily accessible for journalists in a more general sense, such tools need to utilize simple and easy‐to‐understand visual interfaces that cater to the exploratory nature of the journalists' activities, for example to allow the incorporation of unconfirmed data that can be used for further investigation [KCCW09, UK15]. A prominent example of such a tool is Overview which allows journalists to analyze large bodies of documents [BISM14].…”
Section: Related Workmentioning
confidence: 99%
“…Before the exploration phase starts, the journalists find themselves in a preparation phase during which they search and/or collect data and develop (first) theories with which to challenge the data. We know from the literature in the field of DDJ that the term workflow is generally used when it comes to data-driven journalism [UK15]. Uskali et al [UK15] identified the following steps: "finding a topic, collecting the data sources, cleaning and analyzing, building & visualizing and publishing the product" [UK15].…”
Section: Reflection Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Data journalism teams can take a number of shapes, from the one-person operation to the dedicated investigations team (Usher, 2016;Uskali & Kuutti, 2015): not only do we need to prepare our students for those, but we also need to prepare them for the inevitable reorganizations and tensions that data journalists face as they negotiate relationships with their colleagues in the wider news organization.…”
Section: The Data Newsroommentioning
confidence: 99%
“…Or do they operate as a service department, providing complementary material such as visualization and interactivity for the day's news? This question provides an opportunity to explore literature on the organization of both multiplatform newsrooms and interactive teams-Uskali and Kuutti's framework provides a useful overview of the options (Uskali & Kuutti, 2015), while Nikki Usher's book Interactive Journalism provides further ethnographic detail (Usher, 2016). During the period of the newsroom, students might be coached to vary their approach, increasing or reducing their independence from the rest of the team, in order to get a varied experience of the different dynamics of different arrangements.…”
Section: The Data Newsroommentioning
confidence: 99%